Shiism - The Religious Form of the Idea for Social Change - Todorova, Bogdana (Research Papers, 2020)
Iran is the bosom of Shi'a. The article aims to trace and analyze the role and place of Islam in Iran, to consider the dogmatic differences between Sunnis and Shiites in the context of the geostrategic rivalry between Iran and Saudi Arabia. It has been suggested that Shiism is the religious form of the idea of social change through an interdisciplinary and problem-thematic approach. Original ideas and literature have been proposed to enrich the Bulgarian scientific knowledge of Shiite Islam, with a scientifically applied effect.
Keywords: Iran; Social transformation; Religious reform; Sunnis; Shiites